Vacancy - Antal, Nimród 1973.; Smith, Mark L.; Lieberman, Hal.; Hal Lieberman Company; Screen Gems (1998-.; Sony Pictures Home Entertainment (Firm.; Magna Vision Inc. (Culver City, Calif. Sony Pictures Home Entertainment ; distributed in the Philippines by MagnaVision, 2007)
David and Amy Fox find themselves stranded in the middle of nowhere when their car breaks down. As luck would have it, they come across a motel. There is something very strange and familiar about the Grade-Z slasher movies that the motel broadcasts for its guests' enjoyment. The set appears to be filmed in the very same room David and Amy are occupying. They come to realize that they are trapped in their room with hidden cameras filming their every move. David and Amy desperately search for a means of escape through locked doors, crawlspaces and underground tunnels, all before they become the newest stars of the mystery filmmaker's next cult classic.
Director of photography, Andrzej Sekula ; editor, Armen Minasian ; music, Paul Haslinger ; costume designer, Maya Lieberman ; production designer, Jon Gary Steele ; visual effects supervisor, Rocco Passionino.
Luke Wilson, Kate Beckinsale, Frank Whaley, Ethan Embry.
MPAA rating: R; for brutal violence and terror, brief nudity, and language.
VCD
Keywords: Automobiles -- Maintenance and repair -- Drama; Motels -- United States -- Drama; Slasher films -- Drama